Implementing a mobile application Quizlet to help Senior High School students learn vocabulary - Prayogi, Alesandro Woisela; Wulandari, Mega (ELT Forum: Journal of English Language Teaching, 2021)
This study analyzed how Quizlet, a digital vocabulary learning platform, was implemented in helping students learn vocabulary and how students perceive the application. There were 13 high school students of a private school in Yogyakarta who took part in this study. The vocabulary studied were taken from the students' course book which was on the level B2 of CEFR. This research employed CAR (Classroom Action Research) as its methodology. The findings of this research suggested that the students were engaged when using Quizlet during the class activity. The mean score of Perceived Usefulness is very high (M= 4.03, SD= 0.86) and Perceived Ease of Use is also very high (M=4.38, SD= 0.75). This indicated that students had favorable views towards the application. The data acquired from the interview also indicated that Quizlet was a practical and easy-to-use learning platform. The application was a one-stop vocabulary learning platform. Moreover, it utilized cutting-edge technology in learning and the application was practical and easy to use. Based on the results mentioned, the researchers strongly recommend that teachers start using Quizlet to help their students learn vocabulary.